Central Retinal Artery Occlusion and Its Visual Prognosis In An African Population-Analytical Comparative Retrospective Study (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: retinal artery occlusion; sudden loss of vision; ocular emergency; eye stroke